PENGARUH PERLAKUAN PENDAHULUAN UBI KAYU DAN CARA FERMENTASI TERHADAP KARAKTERISTIK MOCAF - Hermanto Hermanto; Nopiarsy; Gatot Priyanto; Dwi Wulan Sari (Journal of Scientech Research and Development, 2023)
The objective of the research was to determine the effect of cassava preliminary treatment and fermentation process on characteristics of mocaf. The research used a factorial completely randomized design and consisting of two factors, namely cassava preliminary treatment (A factor with the following levels: scraped (A1) and non-scraped cassava (A2) tuber) and fermentation process (B factor with the following levels: spontaneous, use of tempe starter and use of Bacillus amyloliquefaciens). The experiment was conducted in triplicates. The following parameters were observed, including physical (gelatinization temperature, viscosity and color), chemical (moisture content, ash content, protein content, reducing sugar content, starch content and crude fiber content) and sensory (test using texture, flavor and color attributes) characteristics with control (brand mokap putri 21 Gunung Kidul Yogyakarta). The results showed that cassava preliminary treatment significantly affected viscosity and sugar reduction. Fermentation process significantly affected viscosity, redness, ash content, protein content, and sugar reduction. Sensory tests significantly affected color. Based on the results of research suggested to use the scrapped mucilage cassava dan B. amyloliquefaciens to good produce mocaf characteristics, they are gelatinization temperature 64.67℃, viscosity 68.00 dPa.s, lightness 92.80%, redness 6.23%, yellowness 9.20%, moisture content 8.23%, ash content 1.23%, protein content 2.23%, sugar reduction 0.33%, starch 21.33%, crude fiber 2.05%, texture 2.63 aroma 2.71, color 2.38.